NASAL SEPTAL DEVIATION: A LITERATURE REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The nose is separated into two nasal cavities by the nasal septum, an osteocartilaginous wall. A mild, asymptomatic septal deviation is regarded as a typical developmental variation that most people experience. Because of the degree of departure taken into account in the reporting studies, the reported global prevalence rates varied greatly. Prior classification schemes have been put up to categorize nasal septal deviations based on the nasal septum's features as viewed both vertically and horizontally. The severity of the deviation may impact nasal airflow in certain people, resulting in blockage or olfactory function impairment. Nasal septal deviation can also manifest clinically as headache, rhinosinusitis, hypertension, obstructive sleep apnea, and breathing noises. While imaging tools are necessary for decision-making, clinical assessment is adequate for diagnosis. Computed tomography (CT) and other radiological imaging methods are used to categorize and evaluate the degree of deviated septum. The alternative for treating nasal septal deviation is surgical correction. The most popular nose corrective treatment, septoplasty, has a low rate of complications and excellent satisfaction. We provide a thorough overview of the idea, presentation, diagnosis, available treatments, and quality of life of individuals with nasal septal deviation in this review.